Penyuluhan Gema Cermat Obat dan Edukasi “Tanya 5 O” di Kalisegoro (BERDAYA Indonesian Journal of Community Empowerment, 2022)
Indonesia is currently battling the Covid-19 pandemic, which has also been declared by the WHO as a global pandemic. One way to prevent the transmission of COVID-19 can be anticipated through the mechanism of increasing the immune system (immune) by consuming health supplements. Health Supplements are part of pharmaceutical preparations whose use must still be controlled so that the desired benefits are as expected. Knowledge of the correct medicine or health supplement is an important thing. Therefore, community service activities are carried out which aim to provide correct information related to medicines. This activity is con- veyed through the tagline “Gema Cermat” and educates the public to actively seek information about drugs consumed by “Tanya 5 O”. The target in this implementation is the Kalisegoro sub-district community, which is represented by members of PKK community as family members who have a big role in maintaining the health of family members. This program was conducted in several steps, which were 1) observation of service partners and preparation of evaluation questionnaires; 2) preparation of facilities and infrastructure; 3) preparation of learning materials and media that will be delivered; and 4) conducting of education. The re- sults achieved from these activities was the statistically significant improvement of participants’ knowledge on how to obtain, use, prepare, and dispose of drugs (p-value 0.0002).